(untitled) (Revista Brasileira Multidisciplinar, 2026)
A careful reading of the Management Plan of a municipality on the coast of Rio de Janeiro revealed the following metaphor: the algae that occur in the Rocky Coasts Natural Monument form a "carpet of varied colors". For a group of scientists linked to a Botany Laboratory, this definition may sound childish and naive. Numerous scientific research laboratories describe in a precise, almost surgical way, all the species that occur in this ecosystem. After all, the worlds of politics, economics, the pharmaceutical industry, and health constantly visit this "carpet". From there, cures can emerge for various diseases or produce scientific evidence capable of putting together a piece of the global climate change puzzle. Wouldn’t forgetting the biological dimension of environmental education mean losing the richness and colors of plurality? What material is the "colored carpet" made of? Could this "carpet" be an agent? We consider that action begins when we are uncomfortable with the realization that the same, despite being colorful, was presented from a homogeneous dimension. We decided, then, to step calmly on this "carpet" to reveal the links between heterogeneous elements, human and non-human, that make up this small and exciting world with its varied colors. In this work, we use the Actor-Network Theory as a theoretical-methodological framework and the Caulerpa racemosa stolon as a starting point and source of inspiration. Methodologically, we carried out the following procedures: i) We described a "carpet" composed of more than 100 species of associated algae; ii) We identified links with Environmental Education actions based on the analysis of documents and interviews with employees of the Department of the Environment and iii) we visited, in an imaginary way, different research laboratories. We conclude that, despite being unusual, the exercise of describing algae as hybrids of nature and culture provides us with an alternative for those who seek to transgress the idea that there are boundaries between natural sciences and society.